Kontribusi Tatanan Islam terhadap Demokrasi Permusyawaran di Indonesia - Inna Junaenah (AHKAM : Jurnal Ilmu Syariah, 2016)
The Contributions of Islamic Order to Deliberative Democracy in Indonesia. Many references indicate the dynamic development of democracy with various definitions and classifications. The founding fathers did not want liberal democracy. Therefore, the consultative democracy was selected as outlined in the formulation of the fourth principle of Pancasila. This decision was considered special because there has been a contribution of Islamic thought. This article describes the principles of Islam in the deliberation that carry deliberative democracy including the meaning and purpose of deliberation, the agency that deliberation, and decision making. Those principles are reflected in the formulation of the fourth principle, the existence of the people’s Consultative Assembly, the membership of the Assembly in 1945 before amendments, and decision making method.DOI: 10.15408/ajis.v16i2.4446